The HEAR‐VA Pilot Study: Hearing Assistance Provided to Older Adults in the Emergency Department. Issue 4 (11th February 2021) - Chodosh, Joshua; Goldfeld, Keith; Weinstein, Barbara E.; Radcliffe, Kate; Burlingame, Madeleine; Dickson, Victoria; Grudzen, Corita; Sherman, Scott; Smilowitz, Jessica; Blustein, Jan
Abstract : BACKGROUND/OBJECTIVES: Poor communication is a barrier to care for people with hearing loss. We assessed the feasibility and potential benefit of providing a simple hearing assistance device during an emergency department (ED) visit, for people who reported difficulty hearing. DESIGN: Randomized controlled pilot study. SETTING: The ED of New York Harbor Manhattan Veterans Administration Medical Center. PARTICIPANTS: One hundred and thirty‐three Veterans aged 60 and older, presenting to the ED, likely to be discharged to home, who either (1) said that they had difficulty hearing, or (2) scored 10 or greater (range 0–40) on the Hearing Handicap Inventory‐Survey (HHI‐S). INTERVENTION: Subjects were randomized (1:1), and intervention subjects received a personal amplifier (PA; Williams Sound Pocketalker 2.0) for use during their ED visit. MEASUREMENTS: Three survey instruments: (1) six‐item Hearing and Understanding Questionnaire (HUQ); (2) three‐item Care Transitions Measure; and (3) three‐item Patient Understanding of Discharge Information. Post‐ED visit phone calls to assess ED returns. RESULTS: Of the 133 subjects, 98.3% were male; mean age was 76.4 years (standard deviation (SD) = 9.2). Mean HHI‐S score was 19.2 (SD = 8.3). Across all HUQ items, intervention subjects reported better in‐ED experience than controls. Seventy‐five percent of intervention subjects agreed or strongly agreed that ability to understand what was said was without effort versus 56% for controls. Seventy‐five percent of intervention subjects versus 36% of controls said clinicians provided them with an explanation about presenting problems. Three percent of intervention subjects had an ED revisit within 3 days compared with 9.0% controls. CONCLUSION: Veterans with hearing difficulties reported improved in‐ED experiences with use of PAs, and were less likely to return to the ED within 3 days. PAs may be an important adjunct to older patient ED care but require validation in a larger more definitive randomized controlled trial.